The Role of Ru and RuO2 in the Catalytic Transfer Hydrogenation of 5-Hydroxymethylfurfural for the Production of 2,5-Dimethylfuran - Jae, Jungho; Zheng, Weiqing; Karim, Ayman M.; Guo, Wei; Lobo, Raul F.; Vlachos, Dionisios G. (WILEY-V C H VERLAG GMBH, 2014)
We have previously shown that 2,5-dimethylfuran (DMF) can be produced selectively from 5-hydroxymethylfurfural in up to 80% yield via catalytic transfer hydrogenation with 2-propanol as a hydrogen donor and Ru/C as a catalyst. Herein, we investigate the active phase of the Ru/C catalyst by using extended X-ray absorption fine structure, X-ray photoelectron spectroscopy, and high-resolution TEM analyses. The results reveal that RuO2 is the dominant phase in the fresh (active) catalyst and is reduced to metallic Ru during the reaction with the hydrogen produced insitu from 2-propanol. The deactivation of the catalyst is correlated with the reduction of the surface of RuO2. Reactivity studies of individual phases (bulk RuO2 and reduced Ru/C catalysts) indicate that RuO2 mainly catalyzes the Meerwein-Ponndorf-Verley reaction of 5-hydroxymethylfurfural that produces 2,5-bis(hydroxymethyl)furan and the etherification of 2,5-bis(hydroxymethyl)furan or other intermediates with 2-propanol and that the reduced Ru/C catalyst has moderate hydrogenolysis activity for the production of DMF (30% selectivity) and other intermediates (20%). In contrast, a physical mixture of the two phases increases the DMF selectivity up to 70%, which suggests that both metallic Ru and RuO2 are active phases for the selective production of DMF. The oxidation of the reduced Ru/C catalyst at different temperatures and the insitu hydrogen titration of the oxidized Ru/C catalysts were performed to quantify the bifunctional role of Ru and RuO2 phases. The mild oxidation treatment of the Ru/C catalyst at 403K could activate the catalyst for the selective production of DMF in up to 72% yield by generating a partially oxidized Ru catalyst.
Keywords: LIQUID FUEL 2,5-DIMETHYLFURAN; TOTAL-ENERGY CALCULATIONS; MEERWEIN-PONNDORF-VERLEY; WAVE BASIS-SET; EFFICIENT PRODUCTION; PHASE HYDROGENATION; BETA ZEOLITE; REDUCTION; RUTHENIUM; BIOMASS